Bow-Tie Analysis in the Management of Tabarru’ Funds Using the Investment Adequacy Ratio (IAR) Indicator: A Case Study on the Sharia Unit of PT ABC Life - Basuki Achmad (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
his study is motivated by the decline in the Investment Adequacy Ratio (RKI) in Indonesia’s life insurance industry during 2018–2020, particularly throughout the Covid-19 pandemic. RKI is a key liquidity indicator that reflects an insurer’s ability, including that of Islamic units, to meet short-term obligations; thus, its deterioration poses significant risk exposure. This research employs a case study method on the Islamic unit of PT ABC Life, focusing on tabarru’ fund management as the primary risk source. Data were collected through document analysis of financial statements, internal risk-management guidelines, and supporting interviews with relevant officers. Risk assessment was conducted using the Bow-Tie method to identify causal factors, escalation elements, and controls, aligned with the ISO 31000 framework. The findings reveal several contributors to the RKI decline, including investment-return volatility, reduced participant contributions, and increased claim burdens during the pandemic. The Bow-Tie analysis effectively maps cause-and-effect relationships and highlights the most relevant mitigation controls. These results offer practical insights for Islamic insurance providers in strengthening liquidity risk management and present an analytical framework applicable to similar conditions across the life insurance industry.